DevForce - Rasheed Hendawi; Mohammad AbuRehan (My University, 2025)
The goal of this graduation project is to design and implement a web-based platform for competitive programming, inspired by the widely-used Codeforces website. This platform will offer users the ability to participate in algorithmic problem-solving contests, submit code in multiple programming languages, receive instant feedback via a judging system, and engage with a community of developers through rankings, discussions, and virtual contests. The core functionality will include user registration and authentication, contest creation and management, problem submissions with automated judging, leaderboards, and user profiles. A responsive, modern user interface will be developed to ensure a seamless experience across both web and mobile devices. To achieve this, the project will utilize React for building a dynamic and interactive frontend, while ASP.NET Core will serve as the backend framework to handle API endpoints, authentication, and business logic. In order to extend the platform's reach to mobile users, a dedicated mobile application will be developed using React Native, ensuring a consistent user experience across Android and iOS. The system’s architecture will follow a micro services pattern where suitable, and all services will be containerized using Docker to ensure portability, scalability, and ease of deployment. Additional technologies such as PostgreSQL (or another relational database), Redis (for caching and queue management), and Nginx (as a reverse proxy and load balancer) may also be integrated as part of the infrastructure. This project aims not only to replicate essential features of platforms like Codeforces, but also to introduce enhancements in usability, user engagement, and educational tools for learners. By the end of the development cycle, CodeChallenge will represent a fully functional, scalable, and extensible system for online programming competitions and skill-building.